2023
DOI: 10.1111/bjh.18616
|View full text |Cite
|
Sign up to set email alerts
|

Sickle red blood cell‐derived extracellular vesicles activate endothelial cells and enhance sickle red cell adhesion mediated by von Willebrand factor

Abstract: Endothelial activation and sickle red blood cell (RBC) adhesion are central to the pathogenesis of sickle cell disease (SCD). Quantitatively, RBC-derived extracellular vesicles (REVs) are more abundant from SS RBCs compared with healthy RBCs (AA RBCs). Sickle RBC-derived REVs (SS REVs) are known to promote endothelial cell (EC) activation through cell signalling and transcriptional regulation at longer terms. However, the SS REV-mediated short-term non-transcriptional response of EC is unclear. Here, we examin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 60 publications
0
22
0
Order By: Relevance
“…Treating HbSS mice with rADAMTS-13 attenuates anemia/hemolysis, inflammation, organ damage, and vascular stasis induced by TNFα, H/R, and heme. A key finding of these reports is that ADAMTS13 reduced stasis and organ damage even when given after the acute trigger [51 ▪▪ ,54 ▪ ], suggesting that ADAMTS-13 is a beneficial treatment for patients during an acute VOE and may provide protection against organ damage. A double-blind, placebo-controlled, phase I clinical trial, called rADAMST-13 in Sickle Cell Disease (RAISE), is enrolling adult SCD patients (NCT 03997760) and will investigate the effect of rADAMTS13 on disease severity markers.…”
Section: Endothelial Von Willebrand Factor: the Invisible Stringmentioning
confidence: 99%
See 1 more Smart Citation
“…Treating HbSS mice with rADAMTS-13 attenuates anemia/hemolysis, inflammation, organ damage, and vascular stasis induced by TNFα, H/R, and heme. A key finding of these reports is that ADAMTS13 reduced stasis and organ damage even when given after the acute trigger [51 ▪▪ ,54 ▪ ], suggesting that ADAMTS-13 is a beneficial treatment for patients during an acute VOE and may provide protection against organ damage. A double-blind, placebo-controlled, phase I clinical trial, called rADAMST-13 in Sickle Cell Disease (RAISE), is enrolling adult SCD patients (NCT 03997760) and will investigate the effect of rADAMTS13 on disease severity markers.…”
Section: Endothelial Von Willebrand Factor: the Invisible Stringmentioning
confidence: 99%
“…These findings were confirmed by two additional models of acute stasis. Using endothelialized microfluidics devices, An et al [54 ▪ ] found that extracellular vesicles derived from sickle RBCs (SS-REVs) increased endothelial VWF levels and adhesion of human sickle RBCs to the endothelium, an effect that was reversed by ADAMTS-13. Treating HbSS mice with ADAMTS-13 after exposure to either heme or SS-REVs attenuated microvascular stasis in the DSFC model [54 ▪ ].…”
Section: Endothelial Von Willebrand Factor: the Invisible Stringmentioning
confidence: 99%
“…In this paper, An Ran et al 1 report on keystone findings in sickle cell disease (SCD) pathophysiology. The authors explored the adhesion processes caused by human sickle erythrocytes and human pulmonary endothelial cells (HPMEC) in vitro and in vivo .…”
Section: Effects On Hpmec Haeme Hemopexin* Adamts‐13#mentioning
confidence: 99%
“…2a,b). We have focused on standardizing these microfluidic assays to measure abnormal blood cell adhesion in whole blood samples and have uncovered significant associations with clinical phenotypes and response to treatment in SCD [56,[64][65][66][67][68][69][70][71][72][73].…”
Section: Existing Microfluidic Assays For Assessing Abnormal Cellular...mentioning
confidence: 99%